MOESM2 of Differential expression of the aryl hydrocarbon receptor pathway associates with craniofacial polymorphism in sympatric Arctic charr - Ahi, Ehsan; Steinhäuser, Sophie; Pálsson, Arnar; Sigrídur Franzdóttir; Sigurdur Snorrason; Maier, Valerie; Jónsson, Zophonías (Figshare, 2015)
Additional file 2: Table S2. Primers designed for cDNA cloning and qPCR study of Arctic charr.